Homocysteine as an independent and dependent causative factor of Cardio Vascular Diseases (International Journal of Food and Nutritional Sciences, 2022)
Homocysteine/homocystine (Hcy), an endogenous sulfur containing non proteinous amino acid synthesized during the catabolism of essential dietary amino acid methionine. Once homocysteine is produced, it metabolized in the body through one of two possible pathways - remethylation or transsulfuration. Plasma homocysteine concentrations may differ, depending on which metabolic homocysteine pathway is preceded in body. Genetics, nutritional status, and life style factors are the major determinants of plasma Hcy levels. Even a mild impairment in remethylation or transsulfuration pathways leads to increase in plasma fasting Hcy concentrations (≥15µmol/litre). The biological relevance of Hcy metabolism and its association with various factors makes it an important candidate pathway for cardio vascular diseases. Elevated levels of Hcy induces endothelial damage, produce vascular inflammation, decreases bioavailability of nitric oxide (NO), increase oxidative stress, and have a cytotoxic effect by modulating vascular cell function. Hcy act as independent biomarker of cardiovascular diseases and can also promote other risk factors such as hypertension and diabetes. B vitamin intake through diet or supplements is considered as the best therapeutic options for lowering elevated Hcy levels in body.